Mechanical improvement of halal gelatin from marine sources - Jaswir, Irwandi; Asari, Aniza; Salleh, Hamzah Mohd. (IIUM Press, 2011)
Gelatin replacement has existed for many years for the vegetarian, halal and kosher markets, but has gained increased interest in the last decade, particularly within Europe with the emergence of bovine spongiform encephalopathy or as known as mad cow disease. Since most commercial gelatins are obtained from either pigskin or cow hide, there has been considerable interest in finding and using alternative substitutes. Hence, extracting gelatin from fish skin as new source of gelatin is highly granted. In this research, two types of marine sources were examined for the highest value of gel strength and viscosity under three mechanical improvement conditions using enzyme transglutaminase, namely, incubation temperature, incubation time, and enzyme concentration. The extracted sample that has excellent gel strength were selected for the optimization of the modification conditions by using Central Composite Design (CCD) by Design Expert v.6.0.8. Hexanchus griseus or shark was found to have the highest value of gel strength which are 2.6g. The analysis revealed that the maximum gel strength from gelatin extract of Hexanchus griseus skin can be reached with these conditions: 6°C, 24 hr and 0.15mg/ml of enzyme concentration.